2019
DOI: 10.1136/bmjebm-2018-111146
|View full text |Cite
|
Sign up to set email alerts
|

Overdiagnosis paradigm: not suitable for decreasing the overuse of antibiotics

Abstract: This paper summarises the discussion during the workshop on ‘Overdiagnosis and overtreatment of infectious diseases in general practice. How and where to break the endless loop?’ The workshop was organised as part of the overdiagnosis conference carried out in August 2018 in Copenhagen, Denmark. During the workshop, participants from all over the world reflected on the challenges of embracing the overdiagnosis paradigm as a tool to advance understanding and to find solutions to the unnecessary use of antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…This result was in line with a previous study that compared the physicians' diagnosis with algorithmic, adjudicated diagnostic criteria for SAP and found that clinicians tend to over-diagnose SAP compared to algorithmbased approaches [16]. Overdiagnosis and overtreatment of SAP inevitably lead to serious repercussions such as excessive and unnecessary antibiotics usage in stroke patients, which often considered the main driver for bacterial resistance and also associated with and increase the economic burden on the patients [28,29]. Clinicians are guided to treat SAP as early as possible.…”
Section: Discussionsupporting
confidence: 88%
“…This result was in line with a previous study that compared the physicians' diagnosis with algorithmic, adjudicated diagnostic criteria for SAP and found that clinicians tend to over-diagnose SAP compared to algorithmbased approaches [16]. Overdiagnosis and overtreatment of SAP inevitably lead to serious repercussions such as excessive and unnecessary antibiotics usage in stroke patients, which often considered the main driver for bacterial resistance and also associated with and increase the economic burden on the patients [28,29]. Clinicians are guided to treat SAP as early as possible.…”
Section: Discussionsupporting
confidence: 88%
“…However, discontinuing an unnecessary antibiotic course is seldom carried out in routine clinical practice because most physicians are concerned about hypothetical negative consequences of discontinuation. Fear of complications is one of the main reasons doctors feel reluctant to stop an antibiotic course despite knowing that this is no longer needed [ 28 ]. Notwithstanding this, only 12% of the respondents considered that the AD practice could lead to more complications and hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“…15,26,27 HCPs acknowledge that while the pressure to 'do something' can be consequential with regard to exacerbating antibiotic resistance, perceived failure to provide care to a patient can be equally if not more devastating. 10 To overcome this, acknowledging the lack of a gold standard for VAP diagnosis but arming clinicians with outcomes of short course (1-3 days) of antibiotic treatment 15,28 based on clinical criteria (and not necessarily culture results) could be a potential opportunity to limit both unnecessary culturing and antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although diagnostic stewardship interventions are being increasingly implemented, accounting for clinician beliefs and behavioral norms in intervention design is important to maximize intervention uptake and impact. 9,10 We studied healthcare provider (HCP) practices and perceptions of challenges associated with VAP diagnosis, and we sought to identify opportunities for diagnostic stewardship.…”
mentioning
confidence: 99%